PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS XI UPW SMK NEGERI 1 JEMBER MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) MATERI PROGRAM LINEAR SEMESTER II TAHUN PELAJARAN 2012/2013 - P, Erica Dian; Susanto, S; Kristiana, Arika Indah (Kadikma, 2014)
Abstract. Cooperative learning type Think Pair Share (TPS) is kind of cooperative learning that is planed to influence the pattern of student interaction. Learning model of type TPS has three stages, that is Thinking, Pairing, and Sharing. The purpose of this research is to know the application of cooperative learning type of TPS material of linear program semester II in 2012/2013 teaching at the students of grade XI UPW section of SMKN 1 Jember. This research design is class action research (CAR) and the method of data collecting using observation, interview, test, and documentation. The result of research indicate that the result of learning activity increase students’ activity of cycle I reach 62,46% and cycle II reach 74,74% while the achievement of student learning at cycle I reach 70,59% and cycle II reach 73,53%. So the model of teaching TPS can increase students’ activity and the achievement of student. Key Words : TPS, linear program, student activity, the achievement of student